1999
DOI: 10.1590/s0037-86821999000200002
|View full text |Cite
|
Sign up to set email alerts
|

Manifestações articulares nas viroses exantemáticas

Abstract: Resumo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
2
4
1
Order By: Relevance
“…The arthropathies associated with the recent/active B19 infection presented short duration (maximum of 10 days), symmetrical distribution and disappeared without sequelae. These clinical features have been recorded in previous studies 36,38 . In our study, the absence of chronic arthropathies associated with parvovirus B19, as previously described 34,36 , could be explained by the fact that a low number of patients (n = 13) with chronic joint symptoms (lasting months or years) were enrolled in the present study.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The arthropathies associated with the recent/active B19 infection presented short duration (maximum of 10 days), symmetrical distribution and disappeared without sequelae. These clinical features have been recorded in previous studies 36,38 . In our study, the absence of chronic arthropathies associated with parvovirus B19, as previously described 34,36 , could be explained by the fact that a low number of patients (n = 13) with chronic joint symptoms (lasting months or years) were enrolled in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…This fact raises the possibility that pathogens not investigated in our study be associated with the disease, as demonstrated in others regions 37,41,48,49 . Because of situations like this, 36,38,40 it has been stressed the importance of making differential diagnosis with arthropathies due to other pathogens, so that proper therapeutic measure can be taken. In our study, interfalangial joints of hands and feet were mostly affected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The confirmed diagnosis of rubella in this sample was 3.9%, lower than the percentage found in Zulia, Venezuela (1998) and in Niteroi, Rio de Janeiro, Brazil (1994 to 1998), from exanthematic diseases, with observed frequencies of 38.2% and 21.0% for rubella, respectively 12,15 . Another survey of suspected dengue cases in Yucatan, Mexico (1988 to 2001) as described by BUSTOS et al 7 showed a detection of 10.0% of subjects with rubella.…”
Section: Discussioncontrasting
confidence: 63%